Strategy towards large two-photon absorption cross-sections for diketopyrrolopyrroles. Issue 4 (8th December 2014) - Purc, Anna; Sobczyk, Krzysztof; Sakagami, Yusuke; Ando, Akihiro; Kamada, Kenji; Gryko, Daniel T.
Abstract : Decorating diketopyrrolopyrroles with strongly electron-rich heterocycles led to donor–acceptor–donor architectures possessing two-photon brightness 850–1900 GM. Abstract : Three quadrupolar donor–acceptor–donor compounds bearing diketopyrrolopyrroles as a central core and exceptionally electron-rich diarylaminofurans and dialkylaminobenzofuran as donors were designed. Straightforward synthesis afforded these dyes in good overall yield. These donor–acceptor–donor systems turned out to be strong red-emitters with fluorescence extending well into the NIR region. Two-photon brightness (850–1900 GM) was found to be larger than for any previously studied diketopyrrolopyrrole dyes.